Bioinformatics analysis to screen for genes related to myocardial infarction - Yang, Liting; Pan, Xuyang; Zhang, Ying; Zhao, Dongsheng; Wang, Liang; Yuan, Guoliang; Zhou, Changgao; Li, Tao; Li, Wei (Frontiers in Genetics, 2022)
Myocardial infarction (MI) is an acute and persistent myocardial ischemia caused by coronary artery disease. This study aimed to screen potential genes related to MI. Three gene expression datasets that related with MI were downloaded from Gene Expression Omnibus database. Differentially expressed genes (DEGs) were screened using the MetaDE package. Afterwards, the modules and genes closely related to MI were screened and gene co-expression network was constructed. Furthermore, Support Vector Machine (SVM) classification model was constructed based on the GSE61145 dataset using e1071 package in R. Totally, 98 DEGs were identified in the MI samples. Afterwards, 3 modules associated with MI were screened and SVM classification model involving 7 genes were constructed. Meanwhile, BCL6, CEACAM8 and CUGBP2 had interactions with each other in gene co-expression network. The ACOX1, BCL6, CEACAM8, CUGBP2 and GPX7 might be the feature genes related to MI.